Membrane electrode and application thereof
By using sulfur and/or nitrogen-modified supported platinum atomic cluster catalyst in PEM electrolytic hydrogen production technology, the problems of large amount of precious metals and low hydrogen production in the electrolytic cell are solved, and the high activity and stability of the membrane electrode are achieved. Reduce costs and promote the commercial application of technology.
Patent Information
- Application Number
- CN202311041366.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-17
- Publication Date
- 2025-02-21
AI Technical Summary
In the existing PEM electrolytic hydrogen production technology, precious metal platinum uses a large amount and high cost, which limits the commercialization process of the technology. At the same time, increasing the hydrogen production of the electrolytic cell requires a large current operation, but the mass transfer and stability of the membrane electrode are difficult to improve.
The membrane electrode consisting of a proton exchange membrane and a supported platinum atomic cluster catalyst modified by sulfur and/or nitrogen is used to improve the dispersion and utilization of platinum through the modification catalyst, enhance the mass transfer capability of the membrane electrode, and improve the long-term operation. stability.
It significantly improves the electrochemical activity and stability of the membrane electrode, reduces the amount of platinum, increases the current density and hydrogen production of the electrolytic cell, reduces costs, and promotes the commercial application of the technology.
Smart Images

Figure CN119491250A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemical technology, and in particular to a membrane electrode and application thereof. Background Art
[0002] PEM water electrolysis technology is recognized as one of the most promising hydrogen production technologies due to its high electrolysis efficiency, safety and reliability, compact structure, and rapid response to renewable energy. In the great development of hydrogen energy, PEM water electrolysis hydrogen production technology has a huge market. Membrane electrode is a key component in PEM water electrolysis hydrogen production technology and plays a vital role in electrolysis efficiency. However, the large amount of precious metals used and high cost limit the commercialization process of PEM water electrolysis. In addition, to increase the hydrogen production of water electrolysis equipment, high current operation of the electrolyzer is very necessary.
[0003] 40% platinum-carbon catalyst is currently the most mature cathode catalyst for PEM water electrolysis. Although the hydrogen evolution process is fast in kinetics, theoretically, a large amount of Pt is not required. However, due to the harsh reaction environment, Pt is easily lost. Therefore, in order to ensure stability, a Pt dosage far higher than the theoretical amount is required. On the other hand, the platinum inside the catalyst particles is difficult to be effectively utilized. In order to ensure the activity of the membrane electrode, a Pt dosage far higher than the theoretical amount is also required to ensure the electrolysis efficiency and long-term operation stability of the electrolyzer. In order to reduce the amount of Pt and realize the high-current operation of the electrolyzer, current research is mainly focused on three aspects. The first is to develop non-precious metal catalysts. However, the activity and stability of non-precious metal catalysts are still a long way from commercial application. The second is to develop single-atom precious metal catalysts. Although single-atom catalysts have high atomic utilization and large platinum electrochemical active area, due to the extremely low loading of single-atom catalysts, the thickness of the catalyst layer in the membrane electrode becomes larger, which affects mass transfer and is not conducive to high-current operation. The stability also needs to be further improved. The third method is to electroplate a thin layer of Pt to increase the electrochemical active area of platinum. However, this method is costly, complicated to operate, and does not have the basis for large-scale application. Therefore, while reducing the amount of precious metals used in the membrane electrode, improving the current density and stability of the membrane electrode is crucial to reducing the cost of the electrolyzer, improving its electrolysis efficiency and hydrogen production, and accelerating commercial applications. Summary of the invention
[0004] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art and to provide a membrane electrode and its application. The membrane electrode is applied in the PEM water electrolysis process and has excellent activity and stability.
[0005] In order to achieve the above objectives, the first aspect of the present invention provides a membrane electrode, which includes a proton exchange membrane and a cathode catalyst layer coated on one side of the proton exchange membrane, and the cathode catalyst layer includes a supported platinum atomic cluster catalyst modified by sulfur and / or nitrogen.
[0006] Preferably, the thickness of the cathode catalyst layer is not greater than 18 microns.
[0007] Preferably, the platinum loading in the cathode catalyst layer is 0.01-0.4 mg / cm 2 .
[0008] Preferably, the sulfur and / or nitrogen modified supported platinum atomic cluster catalyst has no Pt characteristic peak in the XRD spectrum, or the ratio of the normalized peak intensity per unit mass of the Pt (111) characteristic peak to the half-maximum full width is not greater than 1.0 and the ratio of the normalized peak intensity per unit mass of the Pt (200) characteristic peak to the half-maximum full width is not greater than 0.8.
[0009] The second aspect of the present invention provides the use of the membrane electrode described in the first aspect in PEM water electrolysis to produce hydrogen.
[0010] Through the above technical scheme, compared with the prior art, the present invention has the following beneficial technical effects.
[0011] (1) The present invention significantly improves the dispersion of platinum and enhances mass transfer in the membrane electrode by using a supported platinum atomic cluster catalyst modified by sulfur and / or nitrogen, which is beneficial to increasing the current density of the electrolytic cell.
[0012] (2) The present invention improves the utilization rate of platinum and can effectively reduce the amount of Pt in the membrane electrode.
[0013] (3) There is a strong interaction between the carrier and Pt in the catalyst of the cathode catalyst layer of the present invention, which significantly improves the stability of the membrane electrode or electrolyzer during long-term operation. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 2 are the polarization curves of the membrane electrode of Example 1 and Comparative Example 1.
[0015] Figure 2 The CO stripping curves of the membrane electrode of Example 1 and Comparative Example 1 are shown.
[0016] Figure 3 The polarization curves of the membrane electrode of Example 2 and Comparative Example 2 are shown.
[0017] Figure 4 The constant current stability curves of the membrane electrode of Example 2 and Comparative Example 2 are shown.
[0018] Figure 5 This is the polarization curve of the membrane electrode of Example 3.
[0019] Figure 6 This is the membrane electrode constant current stability curve of Example 3.
[0020] Figure 7The polarization curves of the membrane electrode of Example 4 and Comparative Example 3 are shown.
[0021] Figure 8 The constant current stability curves of the membrane electrode of Example 4 and Comparative Example 3 are shown. DETAILED DESCRIPTION
[0022] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0023] A first aspect of the present invention provides a membrane electrode, which comprises a proton exchange membrane and a cathode catalyst layer coated on one side of the proton exchange membrane, wherein the cathode catalyst layer comprises a supported platinum atomic cluster catalyst modified by sulfur and / or nitrogen.
[0024] In the present invention, the platinum atom cluster catalyst refers to a catalyst in which the platinum metal particles do not have regular lattice fringes. Having lattice fringes means that the Pt particles exist in the form of nanocrystals.
[0025] In the present invention, the regular lattice fringes refer to the observation of platinum particles with lattices by TEM or STEM, and the lattice fringes are parallel, which is considered to have regular lattice fringes. Figure 1-7 As shown by the black parallel lines in the middle, it is considered to contain regular lattice fringes.
[0026] In the present invention, as long as the cathode catalyst layer includes a supported platinum atom cluster catalyst modified by sulfur and / or nitrogen, it is not required that all catalysts in the cathode catalyst layer are supported platinum atom cluster catalysts modified by sulfur and / or nitrogen. Preferably, all catalysts in the cathode catalyst layer are platinum-carbon catalysts modified by sulfur and / or nitrogen. More preferably, the platinum metal particles with regular lattice fringes in the platinum-carbon catalyst do not exceed 60%, preferably less than 50%, more preferably less than 40%, and further preferably less than 20% or less than 10%. Specifically, the lattice fringes can be confirmed by observation under TEM or STEM (preferably AC-TEM or AC-STEM).
[0027] According to a preferred embodiment of the present invention, the thickness of the cathode catalyst layer is not more than 18 microns, preferably 1-15 microns, for example, 1 micron, 3 microns, 5 microns, 7 microns, 10 microns, 12 microns, 15 microns. The membrane electrode provided by the present invention has a thinner cathode catalyst layer, which is more conducive to mass transfer and heat transfer during the operation of the electrolyzer, thereby achieving high current density operation. In the present invention, the thickness of the cathode catalyst layer is obtained by observing the cross section of the membrane electrode with a scanning electron microscope.
[0028] The present invention also provides a membrane electrode, the membrane electrode comprising a proton exchange membrane and a cathode catalyst layer coated on one side of the proton exchange membrane, the cathode catalyst layer comprising a nitrogen-modified platinum-carbon catalyst and / or a sulfur-modified platinum-carbon catalyst;
[0029] The nitrogen-modified platinum-carbon catalyst comprises nitrogen-modified conductive carbon black and platinum metal supported thereon, wherein the nitrogen-modified platinum-carbon catalyst has no Pt characteristic peak in the XRD spectrum, or the ratio of the unit mass platinum normalized peak intensity of the Pt (111) characteristic peak to the half-maximum full width is not greater than 1.0 and the ratio of the unit mass platinum normalized peak intensity of the Pt (200) characteristic peak to the half-maximum full width is not greater than 0.8, and the Pt 4f 7 / 2 characteristic peak in the XPS spectrum is located above 71.6 eV;
[0030] The sulfur-modified platinum-carbon catalyst comprises sulfur-modified conductive carbon black and platinum metal supported thereon, wherein the sulfur-modified platinum-carbon catalyst has no Pt characteristic peak in an XRD spectrum, or a ratio of a unit mass of platinum normalized peak intensity to a half-maximum full width of a Pt (111) characteristic peak is not greater than 0.8, and a ratio of a unit mass of platinum normalized peak intensity to a half-maximum full width of a Pt (200) characteristic peak is not greater than 0.5, and a Pt 4f 7 / 2 characteristic peak in an XPS spectrum is located above 71.6 eV.
[0031] According to a preferred embodiment of the present invention, the platinum loading in the cathode catalyst layer is 0.01-0.4 mg / cm 2 , preferably 0.01-0.1 mg / cm 2 . The platinum loading amount described in the present invention refers to the content of platinum in the cathode catalyst layer per unit area. Compared with the prior art, the platinum loading amount in the cathode catalyst layer described in the present invention is significantly lower, which reduces costs while ensuring the electrolysis effect. The platinum loading amount in the cathode catalyst layer described in the present invention is obtained by a handheld XRF analyzer and ICP (testing after dissolving Pt in the catalyst layer on a specific area of the membrane electrode).
[0032] According to a preferred embodiment of the present invention, the electrochemical active area of platinum in the membrane electrode measured by CO stripping method is not less than 100m 2 / g Pt , preferably 100-200m 2 / gPt In the present invention, the electrochemically active area of platinum refers to the active surface area that can participate in electrochemical reactions. The membrane electrode provided by the present invention has a larger electrochemically active area of platinum, which improves the utilization rate of platinum and reduces the amount of Pt in the membrane electrode.
[0033] In the present invention, the electrochemical active area of platinum in the membrane electrode is measured by the CO stripping method. Specifically, nitrogen is introduced into the side of the membrane electrode to be tested until saturated, and then CO is introduced until the catalyst layer is saturated and adsorbed, and then nitrogen is switched to purge to remove free CO, and then the test is performed at 0.05-1.2V at 50mV / s. The integrated charge Q is obtained according to the CO stripping area, and the electrochemical active area (ECSA) is calculated according to the formula: Q / (0.42×m Pt ×10000) to calculate the electrochemical active area per unit mass of platinum. It should be pointed out that the electrochemical active area of platinum calculated by CO stripping method is about 10% lower than that obtained by testing under inert atmosphere, and because the catalyst layer thickness in the membrane electrode is large and there is mass transfer effect, the electrochemical active area of Pt measured in the membrane electrode is about 50%-60% of the electrochemical active area of Pt in the catalyst measured in the rotating disk electrode.
[0034] According to a preferred embodiment of the present invention, when the platinum content in the catalyst is less than or equal to 20 wt %, the electrochemical active area of platinum in the membrane electrode measured by CO stripping method is not less than 120 m 2 / g Pt , more preferably not less than 130m 2 / g Pt , more preferably 130-200m 2 / g Pt .
[0035] According to the present invention, preferably, the cathode catalyst layer may contain other additives in addition to the platinum-carbon catalyst. There is no particular limitation on the type of the additives, which may be various additives conventionally used in the art, such as ionomers.
[0036] Preferably, the cathode catalyst layer comprises a sulfur and / or nitrogen modified supported platinum atom cluster catalyst and an ionomer, and based on the total amount of the cathode catalyst layer, the content of the sulfur and / or nitrogen modified supported platinum atom cluster catalyst is 65-85 wt%, and the content of the ionomer is 15-35 wt%.
[0037] The present invention has a wide range of choices for the type of ionomer, for example, the ionomer can be provided by removing the solvent from a Nafion solution.
[0038] The present invention has no particular limitation on the coating method of the cathode catalyst layer on one side of the proton exchange membrane, and various coating methods commonly used in the art may be used, preferably spraying, scraping or screen printing.
[0039] The present invention has no particular limitation on the parameters of the coating process, as long as a cathode catalyst layer having the above parameters can be obtained by coating. Those skilled in the art can make an adaptive selection based on the above disclosure.
[0040] According to a preferred embodiment of the present invention, the cathode catalyst layer is obtained by coating the slurry of the cathode catalyst layer on one side of the proton exchange membrane and drying. The drying described in the present invention is used to remove the solvent in the slurry of the cathode catalyst layer, and its specific operation is not particularly limited. It can be carried out during the coating process, that is, heating while coating (such as drying), or the drying can be carried out after the coating is completed. Those skilled in the art can make appropriate choices based on actual production.
[0041] According to a preferred embodiment of the present invention, the slurry of the cathode catalyst layer includes a supported platinum atom cluster catalyst modified with sulfur and / or nitrogen, an ionomer solution (such as a Nafion solution) and a solvent.
[0042] The ionomer solution (e.g., Nafion solution) is used for conducting protons and bonding catalysts. There is no particular limitation on the source of the Nafion solution, which can be obtained commercially. The amount of the ionomer solution (e.g., Nafion solution) can be selected in a wide range. Preferably, the mass amount of the ionomer solution (e.g., Nafion solution) is 3.5-11 times that of the supported platinum atom cluster catalyst modified by sulfur and / or nitrogen.
[0043] Preferably, the solvent comprises water and a dispersing solvent, and the dispersing solvent is preferably selected from C1-C4 alcohols. Further preferably, the dispersing solvent is isopropanol and / or ethanol. The volume ratio of water to the dispersing solvent is 1:1.5-4.
[0044] The present invention has a wide range of selection for the amount of the solvent, based on the purpose of achieving uniform coating of the catalyst layer on the proton exchange membrane. Preferably, the amount of the solvent is such that the content of the catalyst in each milliliter of slurry is 5-150 mg.
[0045] According to a preferred embodiment of the present invention, the sulfur and / or nitrogen modified supported platinum atomic cluster catalyst has no Pt characteristic peak in the XRD spectrum, or the ratio of the normalized peak intensity per unit mass of the Pt (111) characteristic peak to the half-maximum full width is not greater than 1.0 and the ratio of the normalized peak intensity per unit mass of the Pt (200) characteristic peak to the half-maximum full width is not greater than 0.8.
[0046] Preferably, in the sulfur and / or nitrogen modified supported platinum atom cluster catalyst, the mass fraction of platinum is 1-70%.
[0047] In the present invention, the sulfur and / or nitrogen modified supported platinum atom cluster catalyst may be a platinum atom cluster catalyst modified with sulfur alone, a platinum atom cluster catalyst modified with nitrogen alone, or a platinum atom cluster catalyst modified with both sulfur and nitrogen.
[0048] Preferably, the sulfur- and / or nitrogen-modified supported platinum atom cluster catalyst comprises a nitrogen-modified platinum-carbon catalyst and / or a sulfur-modified platinum-carbon catalyst.
[0049] Preferably, the nitrogen-modified platinum-carbon catalyst comprises nitrogen-modified conductive carbon black and platinum metal supported thereon, and the nitrogen-modified platinum-carbon catalyst has no Pt characteristic peak in the XRD spectrum, or the ratio of the unit mass platinum normalized peak intensity of the Pt (111) characteristic peak to the half-maximum full width is not greater than 1.0 and the ratio of the unit mass platinum normalized peak intensity of the Pt (200) characteristic peak to the half-maximum full width is not greater than 0.8, and the Pt 4f 7 / 2 characteristic peak in the XPS spectrum is located above 71.6 eV.
[0050] Preferably, the sulfur-modified platinum-carbon catalyst comprises sulfur-modified conductive carbon black and platinum metal supported thereon, and the sulfur-modified platinum-carbon catalyst has no Pt characteristic peak in the XRD spectrum, or the ratio of the unit mass platinum normalized peak intensity of the Pt (111) characteristic peak to the half-maximum full width is not greater than 0.8 and the ratio of the unit mass platinum normalized peak intensity of the Pt (200) characteristic peak to the half-maximum full width is not greater than 0.5, and the Pt 4f 7 / 2 characteristic peak in the XPS spectrum is located above 71.6 eV.
[0051] Specifically, in the nitrogen-modified platinum-carbon catalyst, "there is no Pt characteristic peak in the XRD spectrum, or the ratio of the unit mass platinum normalized peak intensity of the Pt (111) characteristic peak to the half-maximum full width is not greater than 1.0 and the ratio of the unit mass platinum normalized peak intensity of the Pt (200) characteristic peak to the half-maximum full width is not greater than 0.8" means that the platinum in the nitrogen-modified platinum-carbon catalyst is at least mostly present in an amorphous phase, but it does not exclude the presence of a small amount of crystalline phase. As above, the presence of a small amount of crystalline phase does not affect the performance of the nitrogen-modified platinum-carbon catalyst in the membrane electrode.
[0052] Specifically, in the sulfur-modified platinum-carbon catalyst, "there is no Pt characteristic peak in the XRD spectrum, or the ratio of the normalized peak intensity per unit mass of the Pt (111) characteristic peak to the half-maximum full width is not greater than 0.8 and the ratio of the normalized peak intensity per unit mass of the Pt (200) characteristic peak to the half-maximum full width is not greater than 0.5" means that the platinum in the platinum-carbon catalyst of the present invention is at least mostly present in an amorphous phase, but it does not exclude the presence of a small amount of crystalline phase. As above, the presence of a small amount of crystalline phase does not affect the performance of the sulfur-modified platinum-carbon catalyst in the membrane electrode.
[0053] In the present invention, the cathode catalyst layer includes a nitrogen-modified platinum-carbon catalyst and / or a sulfur-modified platinum-carbon catalyst, which means that the cathode catalyst layer may include a nitrogen-modified platinum-carbon catalyst alone, may include a sulfur-modified platinum-carbon catalyst alone, or may include both a nitrogen-modified platinum-carbon catalyst and a sulfur-modified platinum-carbon catalyst. When both a nitrogen-modified platinum-carbon catalyst and a sulfur-modified platinum-carbon catalyst are included, there is no particular limitation on the content of each of the two, and any combination of the two is within the scope of protection of the present invention.
[0054] The present invention has a wide selection range for the content of platinum in the platinum-carbon catalyst. Considering the effect and cost comprehensively, preferably, in the nitrogen-modified platinum-carbon catalyst, the mass fraction of platinum is 1-20%, preferably 1-15%, more preferably 5-15%, and further preferably 6-10%, based on the total mass of the nitrogen-modified platinum-carbon catalyst. Preferably, in the sulfur-modified platinum-carbon catalyst, the mass fraction of platinum is 5-70%, more preferably 6-60%, and further preferably 7-40%, based on the total mass of the sulfur-modified platinum-carbon catalyst.
[0055] According to a preferred embodiment of the present invention, when the platinum content of the nitrogen-modified platinum-carbon catalyst is less than 6 mass %, the ratio of the normalized peak intensity per unit mass of the Pt (111) characteristic peak to the half-maximum full width is not greater than 0.5 and the ratio of the normalized peak intensity per unit mass of the Pt (200) characteristic peak to the half-maximum full width is not greater than 0.4.
[0056] Preferably, the nitrogen element in the nitrogen-modified conductive carbon black exists in the form of pyrrolic nitrogen. Specifically, the XPS analysis of the nitrogen-modified platinum-carbon catalyst of the present invention only has characteristic peaks of pyrrolic nitrogen, but does not have characteristic peaks of other types of nitrogen.
[0057] According to the present invention, preferably, the nitrogen content in the nitrogen-modified conductive carbon black is 0.1-10% by mass, preferably 0.2-5% by mass.
[0058] According to the present invention, preferably, the nitrogen-modified conductive carbon black comprises conductive carbon black and nitrogen and oxygen elements compounded therein. Preferably, the nitrogen-modified conductive carbon black of the present invention does not contain other compound elements except nitrogen. Here, the "compound elements" in the present invention refer to nitrogen, phosphorus, boron, sulfur, fluorine, chlorine, bromine and iodine. More preferably, the nitrogen-modified conductive carbon black is composed of conductive carbon black and nitrogen and oxygen elements compounded therein.
[0059] According to the present invention, preferably, the nitrogen-modified platinum-carbon catalyst has a N 1s Except for the characteristic peak between 399-400.5eV, there is no other characteristic peak between 395-405eV.
[0060] The nitrogen-modified platinum-carbon catalyst described in the present invention is also described in detail in Chinese patent application 202210168801.3. The present invention hereby quotes all of 202210168801.3 to illustrate the present invention. The characterization method of the above parameters of the nitrogen-modified platinum-carbon catalyst is the same as 202210168801.3, which will not be repeated here.
[0061] According to a preferred embodiment of the present invention, in the sulfur-modified platinum-carbon catalyst, the total sulfur content in the sulfur-modified conductive carbon black is greater than or equal to the surface sulfur content, preferably the total sulfur content is more than 1.2 times the surface sulfur content, more preferably more than 1.5 times.
[0062] In the preferred sulfur-modified platinum-carbon catalyst of the present invention, by constructing a new conductive carbon black carrier structure modified by elemental sulfur, it is more conducive to loading platinum inside the carrier, so that the platinum-carbon catalyst has better electrocatalytic performance. More preferably, the total sulfur content in the sulfur-modified conductive carbon black is more than 1.7 times, more than 2 times, more than 3 times, etc., of the surface sulfur content, for example, 1.5-10 times. Wherein, the surface sulfur content represents the sulfur mass fraction measured by XPS analysis, and the total sulfur content represents the sulfur mass fraction measured by a sulfur-carbon analyzer.
[0063] Preferably, the total sulfur content in the sulfur-modified conductive carbon black is 0.1-8% by mass, more preferably 0.5-6% by mass.
[0064] Preferably, the surface sulfur content of the sulfur-modified conductive carbon black is 0.1-6% by mass, preferably 0.5-3% by mass.
[0065] The sulfur-modified platinum-carbon catalyst of the present invention may have a total sulfur content of, for example, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.5, 3, 3.5, 4, 4.5, 5, 6, 7, 8, 9 or 10 times the surface sulfur content. In addition, the total sulfur content may be 0.4 mass%, 0.5 mass%, 1 mass%, 1.5 mass%, 2 mass%, 3 mass%, 4 mass%, 5 mass%, 6 mass%, 7 mass% or 8 mass%, etc.; the surface sulfur content may be 0.1 mass%, 0.5 mass%, 1 mass%, 1.5 mass%, 2 mass%, 3 mass%, 4 mass%, 5 mass% or 6 mass%, etc.
[0066] Preferably, based on the total mass of the sulfur-modified platinum-carbon catalyst, the mass fraction of platinum is 5-70%, preferably 5-60%, more preferably 6-50%, and further preferably 7-40%.
[0067] Preferably, when the platinum content of the sulfur-modified platinum-carbon catalyst is less than 10 mass%, there is no Pt characteristic peak in the XRD spectrum of the sulfur-modified platinum-carbon catalyst, or the ratio of the unit mass platinum normalized peak intensity of the Pt (111) characteristic peak to the half-maximum full width is not greater than 0.6 and the ratio of the unit mass platinum normalized peak intensity of the Pt (200) characteristic peak to the half-maximum full width is not greater than 0.4.
[0068] Preferably, the sulfur-modified platinum-carbon catalyst has a Pt 4f7 / 2 characteristic peak located above 71.7 eV, preferably above 71.9 eV in the XPS spectrum. The above XPS spectrum refers to the XPS spectrum corrected with the C1s peak located at 284.3 eV. Under normal circumstances, such as when platinum is loaded on a carbon carrier without composite elements, the Pt 4f 7 / 2 characteristic peak is located near 71.4 eV, which indicates that the sulfur-modified platinum-carbon catalyst of the present invention has a Pt 4f 7 / 2 characteristic peak shifted to high electron volts by more than 0.3 eV, preferably more than 0.5 eV in the XPS spectrum.
[0069] Preferably, the platinum-carbon catalyst of the present invention does not contain any other active metal elements except platinum.
[0070] According to the present invention, preferably, the sulfur-modified conductive carbon black comprises conductive carbon black and sulfur and oxygen elements compounded therein. Furthermore, the sulfur-modified conductive carbon black of the present invention preferably does not contain other compound elements except sulfur. More preferably, the sulfur-modified conductive carbon black consists of conductive carbon black and sulfur and oxygen elements compounded therein.
[0071] The sulfur-modified platinum-carbon catalyst described in the present invention is also described in detail in Chinese patent applications 202211515045.3 and 202211515010.X. The present invention hereby fully references 202211515045.3 and 202211515010.X to illustrate the present invention. The characterization method of the above parameters of the sulfur-modified platinum-carbon catalyst is the same as 202211515045.3 and 202211515010.X, which will not be repeated here.
[0072] As the conductive carbon black that can be used in the present invention, one or more of ordinary conductive carbon black (Conductive Blacks), super conductive carbon black (Super Conductive Blacks) or extra conductive carbon black (Extra Conductive Blacks) can be used, such as Ketjen black, Cabot conductive carbon black (Cabot, Black pearls, etc.), Oliron conductive carbon black (HIBLACK, PRINTEX, etc.), etc., specifically, it can be one or more of EC-300J, EC-600JD, ECP600JD, VXC72, VXC72R, Black pearls 2000, PRINTEX XE2-B, PRINTEX L6 and HIBLAXK 40B2.
[0073] The present invention has no limitation on the preparation method and source of the conductive carbon black, which may be acetylene black, furnace black, or the like.
[0074] Preferably, in the XPS analysis of the conductive carbon black, the oxygen content is greater than 4% by mass, for example, 5-12% by mass.
[0075] Preferably, the resistivity of the conductive carbon black is less than 10Ω·m, preferably less than 5Ω·m, more preferably less than 3Ω·m, and further preferably 0.01-1Ω·m.
[0076] Preferably, the specific surface area of the conductive carbon black is 200-2000m 2 / g, preferably 220-1500m 2 / g. The specific surface area can be measured by the BET method.
[0077] The preparation method of the supported platinum atom cluster catalyst modified by sulfur and / or nitrogen in the present invention has a wide range of selection, and as long as the above parameter limitations are met, it is more conducive to improving the performance of the membrane electrode of the present invention. Preferably, the preparation method of the supported platinum atom cluster catalyst modified by sulfur and / or nitrogen comprises the following steps:
[0078] (1) nitrogen-modifying and / or sulfur-modifying conductive carbon black to obtain nitrogen-modified conductive carbon black and / or sulfur-modified conductive carbon black;
[0079] (2) removing the solvent from the uniform mixed solution containing nitrogen-modified conductive carbon black and / or sulfur-modified conductive carbon black, a platinum source and a solvent to obtain a precursor material;
[0080] (3) heat treating the precursor material obtained in step (2) at 80-200° C. for 1-4 h in a reducing atmosphere to obtain a platinum atomic cluster catalyst;
[0081] Wherein, in step (1), the nitrogen modification of the conductive carbon black comprises: after the conductive carbon black is contacted with a nitrogen source in an aqueous solution, the water is removed, and the obtained product is subjected to high temperature treatment under an inert atmosphere to obtain nitrogen-modified conductive carbon black; preferably, the conditions of the high temperature treatment include: a temperature of 1000-1500° C. and a constant temperature time of 0.5-10 h;
[0082] Wherein, in step (1), sulfur-modifying the conductive carbon black comprises: impregnating the conductive carbon black with a solution containing sulfur at 10-80° C. for 1-5 hours, and drying the impregnated product to obtain sulfur-modified conductive carbon black.
[0083] Preferably, the nitrogen source is ammonia water and / or urea, and the mass ratio of the conductive carbon black to the nitrogen source calculated by the mass of the nitrogen element is 30:1-1:2.
[0084] Preferably, the solvent in the sulfur-containing solution is CCl 4 , CS 2 , cyclohexane, and n-hexane.
[0085] More preferably, the concentration of sulfur in the sulfur-containing solution is 0.0004-0.02 g / mL.
[0086] Preferably, the amount of sulfur used is 0.005-0.06 g relative to 1 g of the conductive carbon black.
[0087] According to the present invention, preferably, in step (2), the platinum source is one or more of chloroplatinic acid, chloroplatinate, tetraamineplatinum acetate and platinum acetylacetonate.
[0088] In step (2), the solvent is preferably one or more of water, an alcohol solvent or a ketone solvent.
[0089] Preferably, the amount of the platinum source used is 0.01-2.4 g in terms of platinum element relative to 1 g of the nitrogen-modified conductive carbon black and / or the sulfur-modified conductive carbon black.
[0090] According to a preferred embodiment of the present invention, in step (3), the reducing atmosphere comprises hydrogen, preferably a mixed atmosphere of hydrogen and an inert gas, more preferably a mixed atmosphere of hydrogen and nitrogen; preferably, hydrogen accounts for 5-30 volume % of the total gas.
[0091] The detailed preparation of the nitrogen-modified platinum-carbon catalyst is the same as described in 202210168801.3, all of which are cited in the present invention and will not be repeated here.
[0092] The detailed preparation of the sulfur-modified platinum-carbon catalyst is the same as described in 202211515045.3 or 202211515010.X, all of which are cited in the present invention and will not be repeated here.
[0093] In the present invention, "carbon black" and "carbon black" are interchangeable technical terms.
[0094] The "inert gas" in the present invention refers to a gas that does not cause any appreciable effect on the properties of the sulfur / nitrogen modified conductive carbon black in the preparation method of the present invention.
[0095] In the present invention, the cathode catalyst layer is coated on the cathode side of the proton exchange membrane, and specifically, the other side of the proton exchange membrane is coated with an anode catalyst layer. The present invention has no particular limitation on the specific selection of the anode catalyst layer, and it can be a conventional selection in the art. The composition selection range of the anode catalyst layer is relatively wide. Preferably, the anode catalyst layer includes an anode catalyst, and the anode catalyst can be any catalyst conventionally used in the art, including but not limited to iridium-based catalysts. The iridium-based catalyst refers to a catalyst with iridium as an active component, and its active component can be only iridium oxide or elemental iridium, and can also contain other metal oxides, and the present invention has no particular limitation on this.
[0096] The specific coating method of the anode catalyst layer may refer to that of the cathode catalyst layer, and the present invention has no particular limitation thereto.
[0097] The second aspect of the present invention provides the application of the membrane electrode described in the first aspect in PEM water electrolysis to produce hydrogen. Specifically, the membrane electrode provided by the present invention can be applied to a PEM electrolyzer. There is no particular limitation on the arrangement of the membrane electrode in the PEM electrolyzer and the specific process and conditions for producing hydrogen. Those skilled in the art can make adaptive selections according to conventional means. Preferably, in the application, the current density is not less than 1A / cm 2 , and more preferably the current density is 1-3A / cm 2 .
[0098] The present invention will be described in detail below by way of examples. The Nafion solution is commercially available from Chemours under the trade name D521CS. The proton exchange membrane is commercially available from DuPont under the trade name N117.
[0099] For the characterization methods of the following examples, the sulfur-modified catalysts are referred to as described in 202211515045.3 or 202211515010.X, and the nitrogen-modified catalysts are referred to as described in 202210168801.3.
[0100] The electrochemical active area of platinum in the membrane electrode is measured by the CO stripping method. Specifically, nitrogen is introduced into the side of the membrane electrode to be tested until saturated, and then CO is introduced until the catalyst layer is saturated and adsorbed, and then nitrogen is switched to purge to remove free CO, and then the test is performed at 0.05-1.2V and 50mV / s. The integrated charge Q is obtained according to the CO stripping area, and the ECSA (electrochemical active area) is calculated according to the formula ECSA = Q / (0.42×m Pt ×10000) to calculate the electrochemical active area per unit mass of platinum.
[0101] Example 1
[0102] Preparation of 40wt% Pt / C catalyst: 0.55g sulfur was dissolved in 70ml cyclohexane to form a homogeneous solution, 9.45g Ketjenblack ECP600JD was dispersed therein, stirred evenly, immersed for 5h, and dried in vacuum at 50°C to obtain sulfur-containing conductive carbon black as a sulfur-containing carbon carrier; 0.40g chloroplatinic acid was dissolved in 20mL water: ethanol volume ratio of 10:1 based on platinum, 0.6g of the above sulfur-containing carbon carrier was dispersed in the chloroplatinic acid solution, stirred and dispersed evenly, stood for 24h, and then placed in a vacuum drying oven for drying; the dried precursor was placed in a tube furnace, heated to 140°C at a rate of 5°C / min, and heated to 140°C at N 2 :H 2 =5:1 atmosphere for 2h, N 2 The temperature is lowered in the atmosphere to obtain a platinum-carbon catalyst. The composition and structural parameter characterization results of the platinum-carbon catalyst refer to Examples 1-4 of 202211515010.X.
[0103] (1) Slurry for preparing the catalyst layer
[0104] Slurry for the cathode catalyst layer: weigh 1 g of 40 wt% Pt / C catalyst, add 26.6 g of water, disperse evenly, add 46.6 g of isopropanol and 9 g of 5 wt% Nafion solution, mix evenly and set aside.
[0105] Anode catalyst layer slurry: weigh IrO 2Add 26.6 g of water to 1 g of catalyst and disperse evenly. Then add 46.6 g of isopropanol and 9 g of 5 wt% Nafion solution and mix evenly for later use.
[0106] (2) Membrane electrode preparation
[0107] The cathode catalyst layer slurry and the anode catalyst layer slurry were coated on both sides of the proton exchange membrane by spraying, and dried to form a cathode catalyst layer (5.5 microns thick) and an anode catalyst layer (18.2 microns thick), so that the platinum loading in the cathode catalyst layer was 0.1 mg / cm 2 The iridium loading in the anode catalyst layer is 1.71 mg / cm 2 The effective area of the membrane electrode is 5 cm 2 The membrane electrode was installed in the electrolytic cell for testing.
[0108] The electrochemical active area of Pt in the membrane electrode was 106 m 2 / g Pt , CO stripping curve is as follows Figure 2 As shown. Ultrapure water was introduced as the electrolyte at 60°C to test the polarization curve of the membrane electrode, as shown Figure 1 As shown, from Figure 1 It can be seen that when the current density is greater than 1A / cm 2 Compared with commercial agents, the membrane electrode prepared with sulfur-containing atomic cluster catalysts requires a lower voltage to achieve the same current density.
[0109] Example 2
[0110] The method of Example 1 is the same as that of Example 1, except that the cathode uses 8 wt% Pt / C catalyst and the amount of platinum used in the cathode catalyst layer is 0.08 mg / cm 2 The effective area of the membrane electrode is 36 cm 2 .
[0111] Preparation of 8wt% Pt / C catalyst: 1g Vulcan XC72 was immersed in 15mL 0.7wt% urea aqueous solution for 24h; dried in an oven at 100°C; then placed in a tubular furnace, heated to 1200°C at a rate of 10°C / min, and treated at a constant temperature for 3h; the nitrogen-modified carbon support was obtained after natural cooling. For the characterization results of the nitrogen-modified carbon support, see Preparation Example 1 of 202210168801.3. 0.08g of chloroplatinic acid was dissolved in 12mL of a solution with a volume ratio of 10:1 of water: ethanol, and 0.92g of the above-mentioned nitrogen-containing carbon support was dispersed in the chloroplatinic acid solution, where it was stirred and dispersed evenly, and after standing for 24h, it was dried in an oven at 60°C to obtain a catalyst precursor. After grinding the precursor, it was placed in a tubular furnace, heated to 140°C, and heated to N 2 :H2 =4:1 atmosphere for 2h, N 2 The temperature was lowered in the atmosphere to obtain a platinum-carbon catalyst with a loading of 8% by mass.
[0112] The electrochemical active area of Pt in the membrane electrode was 122 m 2 / g Pt , ultrapure water was passed through the membrane electrode at 65°C to test the polarization curve, such as Figure 3 As shown, from Figure 3 It can be seen that when nitrogen-containing atomic cluster catalysts are used, the amount of platinum in the membrane electrode is reduced to the amount used in commercial agents (generally the amount used in commercial agents is 0.4-1 mg / cm 2 ) is less than 20% of the original current density, the voltage required to achieve the same current density is lower, and the advantage is more obvious at high current density. 2 The stability of the membrane electrode under constant current, such as Figure 4 As shown, from Figure 4 It can be seen that after 116 hours of stability testing, the membrane electrode prepared by the nitrogen-containing atomic cluster catalyst has no performance attenuation, and its performance is getting better and better, with excellent stability.
[0113] Example 3
[0114] The method of Example 1 is the same as that of Example 1, except that the cathode uses a 10 wt% Pt / C catalyst and the amount of platinum used in the cathode catalyst layer is 0.013 mg / cm 2 The effective area of the membrane electrode is 5 cm 2 .
[0115] Preparation of 10wt% Pt / C catalyst: Dissolve 0.25g sulfur in 70ml cyclohexane to form a homogeneous solution, disperse 9.75g Ketjenblack ECP600JD therein, stir evenly, immerse for 5h, and vacuum dry at 50°C to obtain sulfur-containing conductive carbon black as a sulfur-containing carbon carrier (same as the preparation of sulfur-containing conductive carbon black in Example 1-2 of 202211515010.X); dissolve 0.10g of chloroplatinic acid in 12mL of water:ethanol in a volume ratio of 10:1, and disperse 0.90g of the above-mentioned sulfur-containing carbon carrier in the chloroplatinic acid solution, stir and disperse evenly, stand for 24h, and dry in an oven at 60°C to obtain a catalyst precursor. Grind the precursor and place it in a tubular furnace, heat it to 140°C, and condense it under N 2 :H 2 =4:1 atmosphere for 2h, N 2 The temperature was lowered in the atmosphere to obtain a platinum-carbon catalyst with a loading of 10% by mass.
[0116] The electrochemical active area of Pt in the membrane electrode was 147 m 2 / g Pt , the polarization curve of the membrane electrode was tested at 80℃, such as Figure 5 As shown, from Figure 5 It can be seen that when sulfur-containing atomic cluster catalysts are used, the amount of platinum in the membrane electrode is reduced to less than 10% of the current commercial amount, and it still has excellent performance. 1.5A / cm in the range of 60-66℃ 2 The stability of the membrane electrode was tested under constant current, such as Figure 6 As shown, from Figure 6 It can be seen that after 70 hours of long-term testing, the membrane electrode performance has not decayed and has excellent stability.
[0117] Example 4
[0118] The method of Example 1 is the same as that of Example 1, except that the cathode uses a 40 wt% Pt / C catalyst and the amount of platinum used in the cathode catalyst layer is 0.025 mg / cm 2 The effective area of the membrane electrode is 5 cm 2 .
[0119] Preparation of 40wt% Pt / C catalyst: same as Example 1.
[0120] The electrochemical active area of Pt in the membrane electrode was 121 m 2 / g Pt , the polarization curve of the membrane electrode was tested at 80℃, such as Figure 7 As shown, from Figure 7 It can be seen that the sulfur-containing atomic cluster catalyst has excellent activity even when the platinum loading of the catalyst is as high as 40%, due to the high dispersion and stability of Pt. When the amount of platinum in the membrane electrode is reduced to less than 10% of the current commercial amount, it still has excellent activity. Compared with the commercial platinum nanocrystalline catalyst with the same loading, it has obvious advantages and better performance at high current density. 2A / cm at 80℃ 2 The stability of the membrane electrode was tested under constant current, such as Figure 8 As shown, from Figure 8 It can be seen that the low-platinum-dosage membrane electrode prepared with sulfur-containing atomic cluster catalysts has significantly better stability than commercial agents.
[0121] Comparative Example 1
[0122] The method of Example 1 was followed, except that the cathode used a commercial 40 wt% Pt / C catalyst (brand name HISPEC4000, produced by Johnson Matthey Company), and the amount of platinum used in the cathode catalyst layer was 0.1 mg / cm 2 .
[0123] The electrochemical active area of Pt in the membrane electrode was 65 m 2 / gPt , CO stripping curve is as follows Figure 2 The polarization curve of the membrane electrode was tested at 60°C, as shown in Figure 1 As shown, from Figure 1 It can be seen that at high current density, the performance of the membrane electrode deteriorates.
[0124] Comparative Example 2
[0125] The method of Example 1 was followed, except that the cathode used a commercial 40 wt% Pt / C catalyst (brand name HISPEC4000, produced by Johnson Matthey Company), and the amount of platinum used in the cathode catalyst layer was 0.4 g / cm 2 .
[0126] The polarization curve of the membrane electrode was tested at 65°C. Figure 3 Show, from Figure 3 It can be seen that at high current density, the performance of the membrane electrode deteriorates because the nanocrystalline catalyst is not conducive to mass transfer. 2 The stability of the membrane electrode was tested under constant current, such as Figure 4 As shown, from Figure 4 It can be seen that after 117 hours of stability testing, it has excellent stability, but the performance has slightly decayed.
[0127] Comparative Example 3
[0128] The method of Example 4 was followed, except that the cathode used a commercial 40 wt% Pt / C catalyst (brand name HISPEC4000, produced by Johnson Matthey Company), and the amount of platinum used in the cathode catalyst layer was 0.025 g / cm 2 .
[0129] The polarization curve of the membrane electrode was tested at 80°C. Figure 7 At 2A / cm 2 The stability of the membrane electrode was tested under constant current, such as Figure 8 It can be seen that when a high-loaded nanocrystalline catalyst is used in a membrane electrode with a low platinum dosage, the stability is extremely poor and cannot meet the application requirements.
[0130] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A membrane electrode, characterized in that: The membrane electrode comprises a proton exchange membrane and a cathode catalyst layer coated on one side of the proton exchange membrane, wherein the cathode catalyst layer comprises a supported platinum atom cluster catalyst modified by sulfur and / or nitrogen.
2. The membrane electrode according to claim 1, wherein: The thickness of the cathode catalyst layer is not greater than 18 microns, preferably 1-15 microns; And / or, the platinum loading in the cathode catalyst layer is 0.01-0.4 mg / cm 2 , preferably 0.01-0.1 mg / cm 2 ; and / or, the electrochemical active area of platinum in the membrane electrode measured by CO stripping method is not less than 100m 2 / g Pt , preferably 100-200m 2 / g Pt ; Preferably, when the platinum content in the catalyst is less than or equal to 20 wt %, the electrochemical active area of platinum in the membrane electrode measured by CO stripping method is not less than 120 m 2 / g Pt , more preferably not less than 130m 2 / g Pt , more preferably 130-200m 2 / g Pt ; Preferably, the cathode catalyst layer comprises a sulfur and / or nitrogen modified supported platinum atomic cluster catalyst and an ionomer. Based on the total amount of the cathode catalyst layer, the content of the sulfur and / or nitrogen modified supported platinum atomic cluster catalyst is 65-85% by weight, and the content of the ionomer is 15-35% by weight.
3. The membrane electrode according to claim 1 or 2, wherein: The cathode catalyst layer is obtained by coating the cathode catalyst layer slurry on one side of the proton exchange membrane and drying it; Preferably, the slurry of the cathode catalyst layer comprises a supported platinum atom cluster catalyst modified with sulfur and / or nitrogen, an ionomer solution and a solvent; Preferably, the mass dosage of the ionomer solution is 3.5-11 times that of the supported platinum atom cluster catalyst modified with sulfur and / or nitrogen; Preferably, the solvent comprises water and a dispersion solvent, and the dispersion solvent is preferably selected from C1-C4 alcohols.
4. The membrane electrode according to any one of claims 1 to 3, wherein: The sulfur and / or nitrogen modified supported platinum atom cluster catalyst has no Pt characteristic peak in the XRD spectrum, or the ratio of the unit mass platinum normalized peak intensity of the Pt (111) characteristic peak to the half-maximum full width is not greater than 1.0, and the ratio of the unit mass platinum normalized peak intensity of the Pt (200) characteristic peak to the half-maximum full width is not greater than 0.8; Preferably, in the sulfur and / or nitrogen modified supported platinum atom cluster catalyst, the mass fraction of platinum is 1-70%.
5. The membrane electrode according to claim 4, wherein: The sulfur- and / or nitrogen-modified supported platinum atom cluster catalyst includes a nitrogen-modified platinum-carbon catalyst and / or a sulfur-modified platinum-carbon catalyst; Preferably, the nitrogen-modified platinum-carbon catalyst comprises nitrogen-modified conductive carbon black and platinum metal supported thereon, the nitrogen-modified platinum-carbon catalyst has no Pt characteristic peak in the XRD spectrum, or the ratio of the unit mass platinum normalized peak intensity of the Pt (111) characteristic peak to the half-maximum full width is not greater than 1.0 and the ratio of the unit mass platinum normalized peak intensity of the Pt (200) characteristic peak to the half-maximum full width is not greater than 0.8, and the Pt 4f 7 / 2 characteristic peak in the XPS spectrum is located above 71.6 eV; Preferably, the sulfur-modified platinum-carbon catalyst comprises sulfur-modified conductive carbon black and platinum metal supported thereon, and the sulfur-modified platinum-carbon catalyst has no Pt characteristic peak in the XRD spectrum, or the ratio of the unit mass platinum normalized peak intensity of the Pt (111) characteristic peak to the half-maximum full width is not greater than 0.8 and the ratio of the unit mass platinum normalized peak intensity of the Pt (200) characteristic peak to the half-maximum full width is not greater than 0.5, and the Pt 4f 7 / 2 characteristic peak in the XPS spectrum is located above 71.6 eV.
6. The membrane electrode according to claim 5, wherein: The conductive carbon black in the nitrogen-modified conductive carbon black and the sulfur-modified conductive carbon black is independently selected from one or more of EC-300J, EC-600JD, ECP600JD, VXC72, VXC72R, Black pearls 2000, PRINTEX XE2-B, PRINTEX L6 and HIBLAXK 40B2; Preferably, in the XPS analysis of the conductive carbon black, the oxygen content is greater than 4 mass %; Preferably, the resistivity of the conductive carbon black is less than 10Ω·m; Preferably, the specific surface area of the conductive carbon black is 200-2000m 2 / g.
7. The membrane electrode according to claim 5 or 6, wherein: The total sulfur content in the sulfur-modified conductive carbon black is greater than or equal to the surface sulfur content, preferably the total sulfur content is more than 1.2 times the surface sulfur content, more preferably more than 1.5 times; Preferably, the total sulfur content in the sulfur-modified conductive carbon black is 0.1-8% by mass, more preferably 0.5-6% by mass; Preferably, the surface sulfur content of the sulfur-modified conductive carbon black is 0.1-6% by mass, preferably 0.5-3% by mass; Preferably, based on the total mass of the sulfur-modified platinum-carbon catalyst, the mass fraction of platinum is 5-70%, preferably 7-40%; Preferably, when the platinum content of the sulfur-modified platinum-carbon catalyst is less than 10% by mass, the sulfur-modified platinum-carbon catalyst does not have a Pt characteristic peak in the XRD spectrum, or the ratio of the unit mass platinum normalized peak intensity of the Pt (111) characteristic peak to the half-maximum full width is not greater than 0.6 and the ratio of the unit mass platinum normalized peak intensity of the Pt (200) characteristic peak to the half-maximum full width is not greater than 0.4; Preferably, the sulfur-modified platinum-carbon catalyst has a Pt 4f 7 / 2 characteristic peak located above 71.7 eV in the XPS spectrum.
8. The membrane electrode according to claim 5 or 6, wherein: In the nitrogen-modified platinum-carbon catalyst, the mass fraction of platinum is 1-20%, preferably 5-15%, based on the total mass of the nitrogen-modified platinum-carbon catalyst; Preferably, when the platinum content of the nitrogen-modified platinum-carbon catalyst is less than 6% by mass, the ratio of the normalized peak intensity per unit mass of the Pt(111) characteristic peak to the half-maximum full width is not greater than 0.5 and the ratio of the normalized peak intensity per unit mass of the Pt(200) characteristic peak to the half-maximum full width is not greater than 0.4; Preferably, the nitrogen element in the nitrogen-modified conductive carbon black exists in the form of pyrrolic nitrogen; Preferably, the nitrogen content of the nitrogen-modified conductive carbon black is 0.1-10% by mass, preferably 0.2-5% by mass; Preferably, the nitrogen-modified platinum-carbon catalyst has a nitrogen content of 1s Except for the characteristic peak between 399-400.5eV, there is no other characteristic peak between 395-405eV.
9. The membrane electrode according to any one of claims 1 to 8, wherein: The preparation method of the supported platinum atom cluster catalyst modified by sulfur and / or nitrogen comprises the following steps: (1) nitrogen-modifying and / or sulfur-modifying conductive carbon black to obtain nitrogen-modified conductive carbon black and / or sulfur-modified conductive carbon black; (2) removing the solvent from the uniform mixed solution containing nitrogen-modified conductive carbon black and / or sulfur-modified conductive carbon black, a platinum source and a solvent to obtain a precursor material; (3) heat treating the precursor material obtained in step (2) at 80-200° C. for 1-4 h in a reducing atmosphere to obtain a platinum atomic cluster catalyst; Wherein, in step (1), the nitrogen modification of the conductive carbon black comprises: after the conductive carbon black is contacted with a nitrogen source in an aqueous solution, the water is removed, and the obtained product is subjected to high temperature treatment under an inert atmosphere to obtain nitrogen-modified conductive carbon black; preferably, the conditions of the high temperature treatment include: a temperature of 1000-1500° C. and a constant temperature time of 0.5-10 h; Wherein, in step (1), sulfur-modifying the conductive carbon black comprises: impregnating the conductive carbon black with a solution containing sulfur at 10-80° C. for 1-5 hours, and drying the impregnated product to obtain sulfur-modified conductive carbon black.
10. The membrane electrode according to claim 9, wherein: The nitrogen source is ammonia water and / or urea, and the mass ratio of the conductive carbon black to the nitrogen source calculated by the mass of the nitrogen element is 30:1-1:
2.
11. The membrane electrode according to claim 9, wherein: The solvent in the sulfur-containing solution is one or more of CCl4, CS2, cyclohexane, and n-hexane; Preferably, the concentration of sulfur in the sulfur-containing solution is 0.0004-0.02 g / mL; Preferably, the amount of sulfur used is 0.005-0.06 g relative to 1 g of the conductive carbon black.
12. The membrane electrode according to any one of claims 9 to 11, wherein: In step (2), the platinum source is one or more of chloroplatinic acid, chloroplatinate, tetraammineplatinum acetate and platinum acetylacetonate; and / or, in step (2), the solvent is one or more of water, an alcohol solvent or a ketone solvent; And / or, relative to 1g of the nitrogen-modified conductive carbon black and / or the sulfur-modified conductive carbon black, the amount of the platinum source used is 0.01-2.4g in terms of platinum element.
13. The membrane electrode according to any one of claims 9 to 12, wherein: In step (3), the reducing atmosphere comprises hydrogen, preferably a mixed atmosphere of hydrogen and an inert gas, more preferably a mixed atmosphere of hydrogen and nitrogen; preferably, hydrogen accounts for 5-30 volume % of the total gas.
14. The membrane electrode according to any one of claims 1 to 13, wherein: The other side of the proton exchange membrane is coated with an anode catalyst layer, which includes an iridium-based catalyst.
15. Use of the membrane electrode according to any one of claims 1 to 14 in PEM water electrolysis to produce hydrogen, preferably in said application, the current density is not less than 1A / cm 2 , and more preferably the current density is 1-3A / cm 2 .
Citation Information
Patent Citations
Platinum-carbon catalyst as well as preparation method and application thereof
CN116646540A
Platinum-carbon catalyst as well as preparation method and application thereof
CN116646544A
Platinum-carbon catalyst as well as preparation method and application thereof
CN116676617A